Estimation of HIV incidence in two Brazilian municipalities, 2013 - Célia Landmann Szwarcwald; Orlando da Costa Ferreira Júnior; Ana Maria de Brito; Karin Regina Luhm; Clea Elisa Lopes Ribeiro; Ana Maria Silva; Ana Maria Salustiano Cavalcanti; Tomoko Sasazawa Ito; Sonia Mara Raboni; Paulo Roberto Borges de Souza Júnior; Gerson Fernando Mendes Pereira (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To estimate HIV incidence in two Brazilian municipalities, Recife and Curitiba, in the year of 2013. METHODS The method for estimating incidence was based on primary information, resulting from the Lag-Avidity laboratory test for detection of recent HIV infections, applied in a sample of the cases diagnosed in the two cities in 2013. For the estimation of the HIV incidence for the total population of the cities, the recent infections detected in the research were annualized and weighted by the inverse of the probability of HIV testing in 2013 among the infected and not diagnosed cases. After estimating HIV incidence for the total population, the incidence rates were estimated by sex, age group, and exposure category. RESULTS In Recife, 902 individuals aged 13 years and older were diagnosed with HIV infection. From these, 528 were included in the study, and the estimated proportion of recent infections was 13.1%. In Curitiba, 1,013 people aged 13 years and older were diagnosed, 497 participated in the study, and the proportion of recent infections was 10.5%. In Recife, the estimated incidence rate was 53.1/100,000 inhabitants of 13 years and older, while in Curitiba, it was 41.1/100,000, with male-to-female ratio of 3.5 and 2.4, respectively. We observed high rates of HIV incidence among men who have sex with men, of 1.47% in Recife and 0.92% in Curitiba. CONCLUSIONS The results obtained in the two cities showed that the group of men who have sex with men are disproportionately subject to a greater risk of new infections, and indicate that strategies to control the spread of the epidemic in this population subgroup are essential and urgent.